Active LC Clamp dv/dt Filter for Voltage Reflection due to Long Cable in Induction Motor Drives - Mini R; Manjiri Joshi; B. Hariram Satheesh; Dinesh M.N. (Institute of Advanced Engineering and Science, 2016)
This paper presents an active LC clamped dv/dt filter to mitigate the over voltages appearing across the motor terminals. The over voltages at motor terminal is due to voltage reflection effect of long motor cable connected between high frequency PWM inverter having high dv/dt switching waveforms and ac motor drives. The voltage reflection due to fast switching transients can be reduced by increasing the rise time and fall time of inverter output voltage pulses. The most commonly available mitigating technique is a passive dv/dt filter between inverter and cable. Since, size, cost and losses of passive LC dv/dt filter is more, an active dv/dt filtering technique is used to reduce over voltage at motor terminals. Active LC clamp filtering technique used here consists of a small LC filter designed for a single motor cable length which can be used for any lengths of cable up to 1000m only by changing the active control of the PWM pulses to achieve the desired voltage slope during voltage transition period. The basic principle of active dv/dt filer used here is to charge and discharge the capacitor in the filter with modified PWM pulses to increase the rise time and fall time of output voltage pulses without any extra devices to handle the transient response of the LC filter. Detailed investigation is carried out by simulation using MATLAB-Simulink software with active control of common LC clamp dv/dt filter suitable for various cable lengths ranging from 100 m to 1000 m. Comparative analysis is done with active dv/dt filter designed with a common LC clamp filter and active LC clamp dv/dt filter designed for various cable lengths and also with diode clamped passive dv/dt filter. The results proves the effectiveness of the active common LC dv/dt filter to mitigate the over voltages at motor terminal for cable lengths up to 1000m.